Use of SSRI, But Not SNRI, Increased Upper and Lower Gastrointestinal Bleeding: A Nationwide Population-Based Cohort Study in Taiwan. Issue 46 (November 2015) - Cheng, Yuan-Lung; Hu, Hsiao-Yun; Lin, Xi-Hsuan; Luo, Jiing-Chyuan; Peng, Yen-Ling; Hou, Ming-Chih; Lin, Han-Chieh; Lee, Fa-Yauh
Abstract : Abstract: Selective serotonin receptor inhibitor (SSRI) and serotonin-noradrenaline reuptake inhibitor (SNRI) users have been reported to have an increased risk of upper gastrointestinal bleeding (UGIB), but their association with lower gastrointestinal bleeding (LGIB) is less studied. This study aimed to analyze the incidence of UGIB and LGIB among SSRI users, SNRI users, and controls. Using the National Health Insurance Research Database of Taiwan, 9753 subjects who were taking serotonin reuptake inhibitors (8809 with SSRIs, and 944 with SNRIs), and 39, 012 age, sex, and enrollment time-matched controls were enrolled at a 1:4 ratio. The log-rank test was used to analyze differences in the cumulative hazard of UGIB and LGIB between groups. Cox proportional hazard regression analysis was used to evaluate the independent risk factors for UGIB and LGIB. During the 10-year follow-up period from 2000 to 2010, SSRI users, but not SNRI users, had significantly higher incidences of UGIB and LGIB than the controls ( P  < 0.001; log-rank test). The use of SSRIs, but not SNRIs, was independently associated with an increased risk of UGIB (hazard ratio [HR]:1.97; 95% confidence interval [CI]: 1.67–2.31) and LGIB (HR: 2.96, 95% CI: 2.46–3.57) after adjusting for age, sex, underlying comorbidities, and medications. The long-term use of SSRIs significantly increased the risk of UGIB and LGIB, and caused more LGIB than UGIB in the general population after adjusting for possible confounding factors, but the association between SNRIs and GIB is insignificant. Further prospective studies are needed to clarify this important issue.